Governance and customer value creation in business solutions. Issue 6 (20th March 2020) - Mooi, Erik; Kashyap, Vishal; van Aken, Marc
Abstract : Purpose: This paper aims to consider the impact of contractual and normative governance mechanisms on recommendation intent in a context of healthcare and professional lighting where repeat business from a customer is absent. The authors suggest both contractual and normative governance can create recommendation intent, but only when sufficient customer value is created. Design/methodology/approach: The authors draw on a combination of survey and archival data from the supplier and customer in the medical equipment and advanced (business) lighting systems industries. The authors analyze the data using seemingly unrelated regression and mediation tests. Findings: Contracts and relational norms can increase customer recommendation intent, but only when the supplier creates customer value. Practical implications: The paper's findings suggest that customers of business solutions are more likely to recommend their supplier when contracts are relatively detailed and when buyers and suppliers attempt to craft strong relational norms, despite service solutions being delivered during a relatively short time span. Originality/value: The extant research on business solutions has focused on extended relationships between exchange partners with a high likelihood of repeated transactions. The authors demonstrate how to govern relationships in a solutions context where the likelihood of repeat business from the same customer is low using contractual and normative governance.